PERSPEKTIF FORENSIK KLINIK TERHADAP PERLUKAAN PADA SEBUAH KASUS KDRT: Studi Kasus - Ahmad Yudianto; Syahroni Syahroni (Masyarakat Hukum Kesehatan Indonesia, 2022)
Incidences of physical, psychological and sexual violence are common in Indonesia and tend to increase. All forms of violence, including domestic violence (KDRT) are violations of human rights and criminal law. KDRT can cause injury to the victim, good, moderate, not to mention psychological trauma. An assessment of the injury in this cases by the clinical forensics is absolutely necessary. A case report of a woman being abused by her husband causing physical and psychological injuries at RSUD dr. Soetomo Surabaya then made a report to the police. Upon examination by a medicolegal forensic expert, a wound that results in illness or an obstacle to carrying out work or living for a while. KDRT in short is an act against someone, causing physical, sexual, or psychological suffering or neglect within the household. Perpetrators can be subject to the PKDRT Law No. 23 of 2004 differs in views that can have the same impact but not in the household scope. Not every violence leaves scars. Even visible wounds have different degrees before the law. The role of medicolegal forensic specialists is needed in clinical forensic cases like this, while the law imposed becomes the authority of the authorities.